Trainee Characteristics Affecting Training Transfer Among the TVET Instructors - Bhurtel, Anup; Bhattarai, Prakash C (Journal of Technical Education and Training, 2023)
This study aims to assess whether perceived training transfer differs across personal and professional attributes of the instructors of technical vocational education and training (TVET) in Nepal. Gender, marital status and age were assessed under personal attributes and the type of institution based on ownership, the locale of the institutions and instructors’ experience were assessed within professional attributes. Survey questionnaire was sent online to 251 instructors across the country who had participated in instructional skills-based training in the past three to 15 months and were engaged in technical education as instructors during the time of the study. Data were analyzed using independent samples t-test for demographic variables with two groups, and analysis of variance along with Brown–Forsythe and Welch tests for variables with more than two groups. Statistically significant results were further substantiated using power analysis. The result concluded that perceived training transfer was higher among female instructors, married instructors, privately owned TVET institutions and instructors with five to 10 years of experience as compared to the new ones.